THE CORRELATION BETWEEN MATERNAL AGE, LEVEL OF EDUCATION, AND OCCUPATIONAL STATUS WITH PREECLAMPSIA INCIDENCE - Nurul Azizah (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Background: Preeclampsia remains a critical contributor to global maternal morbidity and mortality, particularly in low-to-middle-income countries. While clinical risk factors are widely recognized, the influence of non-clinical socio-demographic variables requires further empirical evidence to optimize early prevention. Aims: This study aimed to analyze the correlation between maternal age, education level, and occupational status with the incidence of preeclampsia. Methods: An analytical observational study with a cross-sectional design was conducted. The study sample consisted of pregnant women selected through purposive sampling. Data were obtained from medical records and structured interviews, subsequently analyzed using Chi-square and multiple logistic regression. Results: The analysis revealed a significant correlation between maternal age and preeclampsia (p < 0.05), with advanced maternal age (>35 years) exhibiting a 3.5 times higher risk (OR = 3.52). Education level showed a moderate negative correlation (r = -0.42, p = 0.012), indicating that lower educational attainment is associated with increased incidence due to limited health literacy. Furthermore, occupational status involving high physical strain was significantly associated with preeclampsia (p = 0.008) with an Odds Ratio of 2.15. Conclusion: Maternal age, education, and occupational status are significant predictors of preeclampsia. These findings suggest that clinical practitioners must integrate socio-demographic profiling into primary care risk stratification to refine antenatal screening and improve maternal health outcomes.